The Relationship Between Nursing Handover and Patient Safety Goals in The Inpatient Room at The Rs Taman Harapan Baru Bekasi in 2022 - Lia Idealistiana; Melani Fitri Aulia (Universitas Malahayati Lampung, 2022)
ABSTRACT Weighing in has a large role in the problem causing medical errors, ineffective weighing can cause many problems related to patients such as errors and violations in patient care safety. Weighing in, or often called operands, is a technique or way to convey and receive a report related to the patient. The inaccuracy of weighing and implementation that has not been optimal are obstacles in achieving patient safety goals. A more in-depth analysis is needed so that the weigh-in becomes better so as to reduce the occurrence of medical errors. The purpose of the study was to determine the relationship between the process of nursing handover with the implementation of patient safety goals in the inpatient room at Taman Harapan Baru Hospital Bekasi in 2022. This study was a descriptive analytic study with a cross sectional. Research time for 1 month. The population used by nurses in one of the inpatient rooms was 30 people. Sampling using a total sampling of 30 people. Data collection used using interviews with questionnaire media. Analysis of the data used is the chi-square test. The results showed that the process of weighing and receiving nurses was in the good category as many as 22 people (73.3%), the majority of patient safety targets were in the good category as many as 20 people (66.7%). There is a significant relationship (significant) between the process of weighing the nurses with the implementation of patient safety goals P value = 0.041 ( 0.05). In conclusion, there is a significant relationship (significant) between the process of weighing and receiving nurses with the implementation of patient safety goals P value = 0.041 ( 0.05). Suggestions for the management of Taman Harapan Baru Bekasi Hospital require an evaluation of the implementation of the nurse weighing process according to Standard Operating Procedures (SOP) to prevent errors in the transfer of information that have an impact on patient safety. Keywords : Handover, Patient Safety, Medical Error ABSTRAK Timbang terima mempunyai peran sebanyak besar dari masalah penyebab medical error, timbang terima yang tidak efektif dapat mengakibatkan banyak permasalahan yang berhubungan dengan pasien seperti kesalahan dan pelanggaran dalam keselamatan perawatan pasien. Timbang terima, atau sering disebut operan merupakan suatu teknik atau cara untuk menyampaikan dan menerima suatu laporan yang berkaitan dengan pasien. Ketidaktepatan timbang terima dan pelaksanaan yang belum optimal menjadi penghambat dalam tercapainya tujuan keselamatan pasien. Perlu analisis yang lebih mendalam agar timbang terima menjadi lebih baik sehingga mengurangi terjadinya kesalahan medis. Tujuan penelitian adalah untuk mengetahui hubungan proses timbang terima perawat dengan pelaksanaan sasaran keselamatan pasien di ruang rawat inap Rumah Sakit Taman Harapan Baru Bekasi Tahun 2022. Penelitian ini merupakan penelitian deskriptif analitik dengan metode cross sectional. Waktu penelitian selama 1 bulan. Populasi yang di gunakan perawat pelaksana di salah satu ruang rawat inap sebanyak 30 orang. Pengambilan sampel menggunakan total sampling sebanyak 30 orang. Pengumpulan data yang digunakan menggunakan wawancara dengan media kusioner. Analisis data yang digunakan adalah uji chi-square. Hasil penelitian menunjukan proses timbang terima perawat berada pada kategori baik sebanyak 22 orang (73,3%), sasaran keselamatan pasien mayoritas pada kategori baik sebanyak 20 orang (66,7%). Terdapat hubungan yang bermakna (significant) antara proses timbang terima perawat dengan pelaksanaan sasaran keselamatan pasien P value = 0,041 ( 0,05). Kesimpulan terdapat hubungan yang bermakna (significant) antara proses timbang terima perawat dengan pelaksanaan sasaran keselamatan pasien P value = 0,041 ( 0,05). Saran bagi pihak manajemen RS Taman Harapan Baru Bekasi memerlukan evaluasi pelaksanaan proses timbang terima perawat sesuai Standar Prosedur Operasional (SOP) untuk mencegah kesalahan dalam transfer informasi yang berdampak pada keselamatan pasien. Kata Kunci : Timbang Terima, Keselamatan Pasien, Medical Eror